2017
DOI: 10.1002/prca.201700015
|View full text |Cite
|
Sign up to set email alerts
|

Nipple aspirate fluid—A liquid biopsy for diagnosing breast health

Abstract: PurposeNipple secretions are protein‐rich and a potential source of breast cancer biomarkers for breast cancer screening. Previous studies of specific proteins have shown limited correlation with clinicopathological features. Our aim, in this pilot study, was to investigate the intra‐ and interpatient protein composition of nipple secretions and the implications for their use as liquid biopsies.Experimental designMatched pairs of nipple discharge/nipple aspirate fluid (NAF, n = 15) were characterized for physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 41 publications
2
30
0
Order By: Relevance
“…Recently, in a series of experiments to optimise protein separation from a NAF sample, Brunoro et al identified 557 different proteins [ 120 ]. The most complete proteomics study was performed by Shaheed et al [ 121 ], identifying more than 1900 unique gene products including mitogenic growth factors (IGF1, IGF2, EGF, PDGFC, PGGFD, TGFβ1, VEGFA), cell adhesion proteins (CEACAMs, NCAM2, ICAM1), established breast cancer biomarkers (EGFR, mucin-1/CA 15-3, mucin-16/CA-125, MUCL1, cytokeratins 5, 8, 14 and 18) as well as 46 candidate biomarkers under investigation by the National Cancer Institute Early Detection Research Network [ 122 ]. A comparison of matched NAF pairs, from a healthy volunteer and patients with benign, DCIS or invasive carcinoma, detected an average of more than 1200 proteins per sample [ 121 ].…”
Section: Naf Proteomicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, in a series of experiments to optimise protein separation from a NAF sample, Brunoro et al identified 557 different proteins [ 120 ]. The most complete proteomics study was performed by Shaheed et al [ 121 ], identifying more than 1900 unique gene products including mitogenic growth factors (IGF1, IGF2, EGF, PDGFC, PGGFD, TGFβ1, VEGFA), cell adhesion proteins (CEACAMs, NCAM2, ICAM1), established breast cancer biomarkers (EGFR, mucin-1/CA 15-3, mucin-16/CA-125, MUCL1, cytokeratins 5, 8, 14 and 18) as well as 46 candidate biomarkers under investigation by the National Cancer Institute Early Detection Research Network [ 122 ]. A comparison of matched NAF pairs, from a healthy volunteer and patients with benign, DCIS or invasive carcinoma, detected an average of more than 1200 proteins per sample [ 121 ].…”
Section: Naf Proteomicsmentioning
confidence: 99%
“…The most complete proteomics study was performed by Shaheed et al [ 121 ], identifying more than 1900 unique gene products including mitogenic growth factors (IGF1, IGF2, EGF, PDGFC, PGGFD, TGFβ1, VEGFA), cell adhesion proteins (CEACAMs, NCAM2, ICAM1), established breast cancer biomarkers (EGFR, mucin-1/CA 15-3, mucin-16/CA-125, MUCL1, cytokeratins 5, 8, 14 and 18) as well as 46 candidate biomarkers under investigation by the National Cancer Institute Early Detection Research Network [ 122 ]. A comparison of matched NAF pairs, from a healthy volunteer and patients with benign, DCIS or invasive carcinoma, detected an average of more than 1200 proteins per sample [ 121 ]. While matched pairs exhibited strong similarity in profile, individuals showed significant differences, confirming the observations by Brunoro et al, using SDS PAGE and 2D-DIGE analysis of NAF [ 123 ].…”
Section: Naf Proteomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…showing different genetic and epigenetic profiles, allowing tumor to adapt to the microenvironment changes, surviving to the treatments and proning cells to spread in the body. In this field, the technology of LB (applied to a fluid produced by breast gland, named nipple aspirate fluids, NAF) highlights the fascinating power of combining basic and clinical research, as pointed out in a wide clinical proteomic study published in this issue of our journal .…”
mentioning
confidence: 99%
“…The LB technology using NAF may represent the outstanding breakthrough of proteomic cancer research revealing novel diagnostic and prognostic applications. In conjunction to metabolomic and degradome profiling, the use of NAF as liquid biopsy approach will improve the detection of changes in the cellular microenvironment of the breast tumors, understanding molecular and biochemical mechanisms which drive breast tumor initiation, maintenance and progression, enhancing the development of novel drug targets and new treatment strategies.…”
mentioning
confidence: 99%